2020
DOI: 10.1111/spol.12584
|View full text |Cite
|
Sign up to set email alerts
|

Family policy and women's employment outcomes in 45 high‐income countries: A systematic qualitative review of 238 comparative and national studies

Abstract: The article reviews the available quantitative evidence on the relationship between explicit family policy and women's employment outcomes in 45 high-income countries between 1980 and 2016. At the methodological level, we gathered 238 papers through a four-stage systematic qualitative review. We included articles published in English in international journals or by leading research institutes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(75 citation statements)
references
References 138 publications
(136 reference statements)
2
70
0
3
Order By: Relevance
“…First, the 'flow' measure 'paid leave duration' includes the duration of paid maternity, parental and home care leave available to mothers and fathers, measured in weeks. This one indicator includes three different sets of policies with different objectives and, as shown in previous work, with different outcomes (Ferragina, 2020;Thévenon and Solaz, 2013). For instance, maternity benefits are long-standing policies with the purpose of protecting maternal health, while home care leaves (or cash-for-care schemes) actually disincentivize parents, in reality mothers, to return to the labour market.…”
Section: Are Stocks Buffers and Flows Conceptually And Empirically Distinguishable?mentioning
confidence: 99%
“…First, the 'flow' measure 'paid leave duration' includes the duration of paid maternity, parental and home care leave available to mothers and fathers, measured in weeks. This one indicator includes three different sets of policies with different objectives and, as shown in previous work, with different outcomes (Ferragina, 2020;Thévenon and Solaz, 2013). For instance, maternity benefits are long-standing policies with the purpose of protecting maternal health, while home care leaves (or cash-for-care schemes) actually disincentivize parents, in reality mothers, to return to the labour market.…”
Section: Are Stocks Buffers and Flows Conceptually And Empirically Distinguishable?mentioning
confidence: 99%
“…In several groups, adolescents even report slightly more traditional ideologies than their parents, which may be because paid and unpaid work practices in families are frequently more traditional than reported gender ideologies. Various family policy measures, such as the individual entitlement to well-paid parental leave of moderate length and high-quality, affordable childcare provision (for reviews, see Ferragina 2020;Ray et al 2010), have been shown to effectively incentivise maternal labour market attachment and fathers' involvement in childcare. Such measures may therefore indirectly promote more egalitarian ideologies among the next generation.…”
Section: Practice Implicationsmentioning
confidence: 99%
“…Over the last five decades, the family policy systems of developed countries have become increasingly diverse and layered into national income transfer and welfare service systems [75]. Public childcare expansion has been "the most remarkable family policy development" [76] (p. 2) and "the most recent and most rapidly expanding component of the family policy package" [77] (p. 21), which has sought to mitigate the social risks of modern society while promoting economic policy efforts by enabling women to participate in working life.…”
Section: Economic and Environmental Aspects Of Family And Child Welfarementioning
confidence: 99%